Chemistry of the Highly Strained Alkene Perfluorobicyclo[2.2.0]hex‐1(4)‐ene. Issue 24 (21st June 2018) - Junk, Christopher P.; He, Yigang; Zhang, Yin; Smith, Joshua R.; Dixon, David A.; Vasiliu, Monica; Lemal, David M.
Abstract : Several varieties of cycloaddition as well as nucleophilic and free radical addition to the highly reactive central bond of the title fluorocarbon (1 ) are described. [2 + 2] Cycloaddition to1 has made available four of the five known representatives of the [2.2.2]propellane ring system, which are rare because of their extreme strain (in the absence of fluorine substitution) and high reactivity. Two of these, a propellanone and a propellene, are first reported here. Quantum mechanical calculations have shed light on many of these transformations. Abstract : An array of additions and cycloadditions of a highly reactive perfluoroalkene is described, and many of these transformations are examined computationally. Among the products are [2.2.2]propellanes.